TOPOLOGICAL DISLOCATIONS IN THE CONTINUUM-LIMIT OF SU(2) LATTICE GAUGE-THEORY - Pugh, D; Teper, M (1989)
We show that the SU(2) lattice topological susceptibility, as calculated using the Phillips and Stone algorithm, is divergent in the continuum limit, when one uses the standard plaquette action. We discuss remedies and implications. © 1989.